Outcome-oriented multi-stakeholder network design: four innovation spaces to accelerate food system transformation - Korner, Jana; Thornton, Philip K.; Klerkx, Laurens (2022)
Multi-stakeholder networks fulfil crucial functions for transforming our food systems in the face of climate change, but there is scant research on how the form of these networks is connected to particular aims. Based on interviews with leaders or founders of 15 multi-stakeholder networks, we build a framework on outcome-oriented network design: We identify four different network designs, which emerge from a framework of ten design variables, each with different characteristics. We coin these network designs ?innovation spaces? and observe the main challenges and trade-offs among and between different sets of design variables. These, as well as the networks? main trajectories over time, lead us to introduce a simple innovation space grid model along the axes of structure and permeability. Each space accommodates a different type of stakeholder interaction which leads to the desired change dynamics and network goals. The concept of innovation spaces provides a differentiated view with regard to how multi-stakeholder networks innovate and learn. We also identify a space for an as yet neglected group, self-organized social movements. The innovation spaces concept can cater for long-term as well as short-term multi-stakeholder initiatives, and reflections on inclusivity and addressing power inequalities. It can help designers and leaders of new and existing networks to take improved decisions on how networks could complement their respective innovation processes, thus accelerating food system transformation.